(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Neopetrosia exigua has received great attention in natural product chemistry. The diversity of N. exigua constituents has been demonstrated by the continued discovery of novel bioactive metabolites such as antimicrobial metabolites. In this study, in order to localise the active component of N. exigua biomass according to the polarity, a sequential gradient partition with different solvents (n-hexane, carbon tetrachloride, dichloromethane, n-butanol, and water) was performed to obtain fractions containing metabolites distributed according to their polarity. The antimicrobial activities of N. exigua fractions were then evaluated using disc diffusion and microdilution methods (influence on the growth curve, Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC)). The results showed that the active metabolites were present in n-hexane, CH2Cl2, n-BuOH, and water fractions. n-hexane, CH2Cl2, and n-BuOH fractions were the most effective fractions. Among microbes tested, Staphylococcus aureus was the most susceptible microbe evaluated. The obtained results are considered sufficient for further study to isolate the compounds represent the antimicrobial activity.